SIKAP DAN PERSEPSI TERHADAP STIGMA NEGATIF PADA ODHA BAGI MASYARAKAT PERKOTAAN DAN PEDESAAN DI SULAWESI TENGGARA - Masluhiya AF, Swaidatul; Irma, Irma; Sabilu, Yusuf (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
HIV or Human Immune Deficiency Virus is a virus that weakens the human immune system which has become a global health problem to date with the number of cases that continues to increase from year to year, both at the international, regional and national and regional levels. The number of people with HIV / AIDS or PLWHA is always increasing every year. HIV / AIDS also always makes sufferers get a negative stigma among the community. The purpose of this study was to look at differences in attitudes and perceptions of negative stigma among PLHIV for urban and rural communities in Southeast Sulawesi. This research is a quantitative study with a comparative design with a population originating from Kelurahan Kemaraya, Kendari City and Lagundi Village, North Buton Regency, Southeast Sulawesi, with a sample of 250 households represented by one respondent per household. Samples were taken by proportional random sampling technique. The questionnaire as a data reference instrument and the collected data were processed statistical data using the Mann Whitney test at a 95% confidence level. The results showed that there was a significant difference between negative attitudes and perceptions of negative stigma among people living with HIV / AIDS for urban and rural communities in Southeast Sulawesi.